INTERNALIZATION of AKHLAKUL KARIMAH VALUES as CORE VALUES for QUALITY ASSURANCE in CONTEMPORARY ISLAMIC BOARDING SCHOOLS - Siti Aimah; Fathiyah Mohd. Fakhruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the strategy of internalizing akhlakul karimah values as core values in the Islamic boarding school education quality assurance system to address the challenges of moral disruption in the contemporary era. Using a qualitative approach with an explanatory case study design, data were collected through in-depth interviews with caretakers, heads of quality assurance, and asatidz, as well as participant observation and documentation. The data were analyzed using an interactive model and data verification using triangulation. The results of the study indicate that Darussalam Blokagung Islamic Boarding School has successfully integrated akhlakul karimah indicators into academic and non-academic quality standards through the “SPI-Plus” (Islamic Boarding School-based Internal Assurance System) mechanism, where student graduation and teacher performance evaluation are not only measured from cognitive aspects, but also from the consistency of ethical behavior, compliance ( ta’dhim ), and community service. The distinction of this study lies in the deconstruction of the western Total Quality Management (TQM) concept which tends to be secular-materialistic into a Sufi-transcendental TQM model that places spiritual piety as the main indicator of institutional quality. The theoretical contribution of this research enriches the treasury of Islamic education management by offering a new formula for contemporary quality assurance, while its practical contribution provides a reference for replication for thousands of Islamic boarding schools in Indonesia in formulating quality standards that do not lose their salaf identity, while having a strong impact on increasing the competitiveness of graduates with character at the national level.